Pengembangan Formula Susu Bubuk dengan Penambahan Kolagen Ikan Berdasarkan Penerimaan Mutu Sensori - Aghitia Maulani; Feri Kusnandar; Sugiyono Sugiyono (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2018)
Collagen is an ingredient that is widely used in food product formulations to provide health effects. Among the sources of collagen is the fish collagen that has potential to be added to powdered milk products. This study aimed to develop powdered milk formula with the addition of fish collagen. Milk powder was treated with the addition of 2%, 2.5%, and 3% fish collagen compared to control (0% collagen). The formulas were evaluated organoleptically by untrained panellist who are consuming milk (n=20) using rating hedonic and intensity of sensory attributes (chocolate aroma, chocolate flavor, milk aroma, milk flavor, sweet taste, and savory taste). The selected formula was then compared to two commercial products without collagen (X and Y) by consumer’s test (n=170) using the Central Location Test (CLT) method for overall acceptance attributes. The results showed that the addition of 2% collagen (formula A) gave overall acceptance which was not significantly different (p>0.05) with that of control. The intensity rating test also showed that the use of collagen 2% had the most closest sensory profile to the control. The sensory acceptance of formula A was not significantly different (p>0.05) compared to commercial product X, but it was significantly better (p<0.05) than that of commercial product Y.